Relations entre maturation sexuelle, structure familiale et revenu par habitant d’un échantillon d’élèves d’El Yopal, Casanare (Colombie) - Marie-José Ireton; Julio César Carrillo; Luis Enrique Caro; Juan Carlos Morales; Roland Hauspie (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The goal of this study is to define the sexual maturation characteristics of a population sample of 864 students (468 females and 396 males) from El Yopal, Casanare-Colombia, and to establish their relationship to two variables: family structure and per capita income. Using the probit method, we determined 1) the sexual development stages, with respect to age and sex, and 2) the age of menarche. We thereby calculated the sexual maturation index for two socio-economic groups (defined by monthly per capita income) and analyzed socio-economic factors —such as family composition, parents’ level of education, revenue stability— and eco-geographical variables. The differences between the socio-economic groups were taken into account only for p values